Confident Supervisors Creating Independent Researchers - Gasson, Susan; Bruce, Christine; Stoodley, Ian; Blacker, Jillian; Winter, Abigail (Open textbook library., 2024)
Confident Supervisors is intended to be both a textbook and a professional development resource for Higher Degree Research supervisors and researcher developers involved in providing workshops and resources to support research supervisors in their practice. Throughout this book, authors introduce different theoretical frameworks and concepts to provide supervisors with tools and strategies for responding to the challenges and opportunities associated with research supervision. It contains chapters written by current supervisors and research support partners who are engaged in the scholarship of supervision and can share the practical and theoretical constructs they employ in their practice. The authors have been drawn from a broad range of higher education and research contexts and contribute understandings of local and global relevance. This openly available eBook responds to turbulent times in higher education, offering practical tips and suggestions for supervisors to pivot to changing contexts.